The Influence of Murottal Al- Quran Exposure to Leydig Cell Of Stressed Male Mice (Mus Musculus) - Meilina Ratna Dianti; Yen Yen Ari Indrawijaya; Fidia Rizkiah Inayatilah; Alifah Nurin Zuhdina (Journal of Islamic Medicine, 2022)
Introduction:  Stress is a body's response experienced by a person due to burdened feelings or oppressed in a particular event. Stress may interfere body's homeostasis. One of them is the spermatogenesis process. Healthy stress management is necessary, for example, by doing murottal Al-Qur'an. Reading Al-Qur'an with tartil delivers a beautiful tone and has a relaxing effect and stress release. This research aims to determine the effect of murottal Al-Qur'an on the amount of Leydig cells on male mice (Mus musculus) who are experiencing stress. The compressor used is noise from the road with an intensity of 85dB, given for 12 hours (18.00-06.00) for 21 days. The therapy used was murottal Al-Quran surah Ar-Rahman verses 1-78, which read by Shaykh Abdurrahman Sudais. In this research there were five categories, they are K+ (not given the stressor and murottal therapy), K- (given noise stressors and not given murottal therapy), P1 (given noise stressors for 12-hours and murottal therapy for 1-hour), P2 (given noise stressor for 12-hours and murottal therapy for 2-hours), P3 (given a stress stressor for 12-hours and murottal therapy for 4-hours). Moreover, observations were done on testicular histology preparations with Hematoxylin Eosin staining in olyvia (c) applications. The number of Leydig cells was examined with a 40x magnification microscope. Cell calculations are done manually with the image raster application. The results revealed that murottal Al-Quran is able to significantly affect the number of Leydig cells (p value = 0,000). Lastly, it can be concluded that there is an influence of murottal Al-Quran on the number of Leydig cells in male mice under stress. Keyword : Stress, Noice, Murottal Al-Aquran, Surah Ar-Rahman, Leydig Cell